PHYTOCHEMICAL ANALYSIS OF RUELLIA PATULA USING GAS CHROMATOGRAPHY‑MASS SPECTROMETRY - C, Karthika; G, Yogeshwari; K, MURUGANANTHAM; S, MANIVANNAN (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Ruellia patula (Jacq.) a medicinally important plant belongs to the family Acanthaceae. Traditionally, the leaves are used in the treatment of many diseases such as insect bites, itches, eye diseases, and skin problems. In the present study, the qualitative and quantitative analysis of bioactive compounds by gas chromatography (GC) and mass spectroscopy (MS) techniques. Methods: The chemical compositions of the ethanol extract of R. patula leaves were investigated using Perkin–Elmer GC‑MS. Result: In the GC‑MS analysis of ethanol extract of R. patula L. reported the presence of 15 compounds. The major compound constituents are 3, 7, 11, 15‑tetramethyl‑2‑hexadecen‑1‑ol (28.75%), and α‑sitosterol (14.35%). Conclusion: Identification of these compounds can help in the development of new drugs. Keywords: Ruellia patula, Ethanol extract, Phytochemical compounds, gas chromatography‑mass spectroscopy analysis, Biological activity of phyto‑components.